2020
DOI: 10.1016/j.heliyon.2020.e05357
|View full text |Cite
|
Sign up to set email alerts
|

PXR is a target of (-)-epicatechin in skeletal muscle

Abstract: Epicatechin (EC) is a flavanol that has shown numerous biological effects such as: decrease risk of cardiovascular dysfunction, metabolism regulation, skeletal muscle (SkM) performance improvement and SkM cells differentiation induction, among others. The described EC acceptor/receptor molecules do not explain the EC's effect on SkM. We hypothesize that the pregnane X receptor (PXR) can fulfill those characteristics, based on structural similitude between EC and steroidal backbone and that PXR activation leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…To isolate (-)-epicatechin-interacting proteins from skeletal muscle, we synthesized an affinity column according to a previously reported method [ 7 ]. For the isolation, a homogenate of C57BL/6 mice quadriceps was incubated overnight (4 °C) with the affinity chromatography column; noninteracting proteins were eliminated after several column washes (10×) with PBS (1×, pH = 7.4), and interacting proteins were detached with an acidic solution (MES, pH = 4.5).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To isolate (-)-epicatechin-interacting proteins from skeletal muscle, we synthesized an affinity column according to a previously reported method [ 7 ]. For the isolation, a homogenate of C57BL/6 mice quadriceps was incubated overnight (4 °C) with the affinity chromatography column; noninteracting proteins were eliminated after several column washes (10×) with PBS (1×, pH = 7.4), and interacting proteins were detached with an acidic solution (MES, pH = 4.5).…”
Section: Methodsmentioning
confidence: 99%
“…Many of the reported EC-induced effects are associated with the activation of intermediaries of specific signaling pathways, such as the mitogen-activated protein kinases (MAPKs), Akt, and AMPK pathways, which may depend on transmembrane receptor activation. Recently, using molecular and functional approaches, we demonstrated that EC interacts with two receptors, the G protein-coupled estrogen receptor (GPER), a transmembrane receptor, [ 5 , 6 ], and the pregnane X receptor (PXR), a nuclear receptor [ 7 ]. EC-induced GPER activity induces vasodilation through increases in nitric oxide synthase activity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PXR may prognosticate for survival in patients undergoing liver transplantation (Amer, McColl et al 2019), perhaps via its effects on tacrolimus metabolism (Stifft, van Kuijk et al 2018). In addition, recent work has highlighted new roles for PXR as a factor promoting radio resistance in cancer (Niu, Cui et al 2022), drug sensitivity or resistance (Creusot, Gassiot et al 2020, Sári, Mikó et al 2020, Matheux, Gassiot et al 2021, Ozawa, Miura et al 2021, and promotes striated and smooth muscle metabolism and physiology (Swales, Moore et al 2012, Ortiz-Flores, Portilla-Martínez et al 2020. Our prior work demonstrated that gut microbe-produced indole metabolites of L-tryptophan (e.g., indole and indole propionic acid) are ligands of PXR (Venkatesh, Mukherjee et al 2014).…”
Section: Brief Historical Perspectivementioning
confidence: 96%
“…The same authors showed that further mechanisms of EC action in the vasculature involve modulation of potassium and calcium channels, which participate in the hyperpolarization and depolarization of vascular smooth muscle cells [ 68 ]. Recent studies of Ortiz-Flores et al have shown that EC interacts with and activates the pregnane X receptor [ 173 ]. There is a limited number of studies that investigated the vascular effects of TX.…”
Section: Cellular and Molecular Mechanisms Of Ec And Tx Action Relmentioning
confidence: 99%